Evaluation of MGIT 960 and the colorimetric-based method for tuberculosis drug susceptibility testing - Morcillo, N. (2010)
SETTING: Dr Cetrángolo Hospital, Buenos Aires Province, Argentina. OBJECTIVE: Evaluation of the BACTEC? Mycobacteria Growth Indicator Tube (MGIT)? 960 system and the colorimetric-based method (CMM) for fi rst- and second line drug susceptibility testing (FL-DST, SL-DST) against Mycobacterium tuberculosis. DESIGN: FL-DST was studied using SIRE MGIT 960. Minimal inhibitory concentrations (MICs) for isoniazid (INH), streptomycin, rifampicin (RMP), ethambutol (EMB) and levofl oxacin (LVX) were also determined by CMM using 3-(4,5-dimethylthiazolyl-2)-2,5-diphenyltetrazolium bromide (MTT). MICs for amikacin (AMK), kanamycin (KM), capreomycin (CPM), ethionamide (ETH), cycloserine, ofl oxacin (OFX), linezolide (LZ) and moxifl oxacin (MFX) were determined on 94 multidrug resistant M. tuberculosis isolates by MGIT 960 and CMM. Statistical methods were applied to define drug susceptible and drug-resistant isolates on the basis of the comparison between results obtained by gold standards. RESULTS: A total of 1626 clinical isolates were studied. Critical drug concentrations could be defi ned in less than 10 days for both CMM and MGIT 960. CMM was cheaper but more laborious than MGIT 960. The highest performances of both methods were achieved for AMK, RMP, OFX, LZ and MFX, followed by INH, ETH, KM, CPM and LVX (tested only by CMM). CONCLUSIONS: Both methods could be implemented as rapid diagnostic tools to detect drug-resistant isolates in clinical practice.